Diabetes care: addressing psychosocial well‐being in young adults with a newly developed assessment tool. Issue 1 (14th January 2020) - Bachmeier, Caroline A. E.; Waugh, Claire; Vitanza, Margaret; Bowden, Trish; Uhlman, Carolyn; Hurst, Cameron; Okano, Satomi; Barrett, Helen; D'Silva, Neisha; D'Emden, Helen; O'Moore‐Sullivan, Trisha
Abstract: Background: Psychosocial assessment should be part of clinic visits for people with diabetes mellitus (DM). Aims: To assess the usage and acceptance of a diabetes psychosocial assessment tool (DPAT) and to profile the clinical and psychosocial characteristics of young people with diabetes. Methods: Over a 12‐month period, young adults (18–25 years) attending diabetes clinic were offered DPAT. The tool embeds validated screening tools including the Problem Areas in Diabetes 20 (PAID‐20) questionnaire, the Patient Health Questionnaire‐4 (PHQ‐4) and the World Health Organization Well‐Being Index‐5 (WHO‐5). Baseline clinical data were collected and questions regarding social support, body image, eating concerns, hypoglycaemia and finances were included. Results: Over the 12 month, the form was offered to 155 participants (64.6% of eligible attendees). The majority (96.1%) had type 1 DM with a mean duration of 10.5 (±5.3 SD) years. Average glycated haemoglobin (HbA1c) was 8.7% (±1.5 SD) (or 71.2 mmol/mol ±16.5 SD). Severe diabetes‐related distress (PAID‐20 ≥ 40) was found in 19.4%. Low WHO‐5 scores (28–50 points) were seen in 14.8%. PHQ‐4 identified 25.8% with anxiety and 16.1% with depression. Significant weight, shape and eating concerns were identified in 27.1, 26.6 and 28.4%, respectively. Serious hypoglycaemia concerns were raised by 4.5%. Conclusion: DPAT revealed a high prevalence of psychosocial stress among young adults with DM. The tool was easy to use and accepted by patients and may aid streamlining referrals to relevant members of a multidisciplinary team.